2020
DOI: 10.1007/s00167-020-06050-0
|View full text |Cite
|
Sign up to set email alerts
|

Length-change patterns of the medial collateral ligament and posterior oblique ligament in relation to their function and surgery

Abstract: Purpose To define the length-change patterns of the superficial medial collateral ligament (sMCL), deep MCL (dMCL), and posterior oblique ligament (POL) across knee flexion and with applied anterior and rotational loads, and to relate these findings to their functions in knee stability and to surgical repair or reconstruction. Methods Ten cadaveric knees were mounted in a kinematics rig with loaded quadriceps, ITB, and hamstrings. Length changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
89
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 38 publications
6
89
0
3
Order By: Relevance
“…The importance of the dMCL in the control of tibial external rotation might be unexpected, in view of its relatively small size and its failure strength being less than that of the sMCL [23]. However, we have found that the fibres of the dMCL are oriented antero-distally from the femur when the tibia is externally rotated, and are obviously stretched by that motion [35] (Fig. 1).…”
Section: Discussionmentioning
confidence: 81%
“…The importance of the dMCL in the control of tibial external rotation might be unexpected, in view of its relatively small size and its failure strength being less than that of the sMCL [23]. However, we have found that the fibres of the dMCL are oriented antero-distally from the femur when the tibia is externally rotated, and are obviously stretched by that motion [35] (Fig. 1).…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, one study [20] described the centre of the femoral sMCL attachment 5 mm posterior and 3 mm proximal to the ME, which is outside the mean limit of the attachment area in the present study. The exact femoral attachment site is important: if a graft is placed posteriorly it will slacken with knee flexion [34], or could be too tight in extension. The centre of the femoral attachment of the sMCL is at the same distance from the distal and posterior surfaces of the medial femoral condyle, which suggests that a reconstruction placed on the ME will be isometric.…”
Section: Discussionmentioning
confidence: 99%
“…and over-constraint of the knee, or an insufficient and loose reconstruction, across the arc of knee motion [3,35]. There are significant differences of isometry, or length-change behaviour, across the widths of each of the medial ligaments [34], so it is apparent that accurate positioning is important if the normal patterns of restraint are to be reproduced.…”
Section: Introductionmentioning
confidence: 99%
“…Na prática clínica a designação ligamento colateral medial é utilizada para identificar o ligamento colateral superficial (LCMs), sendo este a estrutura mais frequentemente lesionada após trauma do joelho. [1][2][3][4][5] Ele pertence a uma unidade ligamentar, miotendinosa e meniscal cujos elementos funcionam em sinergia: complexo medial do joelho (CMJ).…”
Section: Introductionunclassified
“…No entanto, sublinhamos que o LCA é o principal estabilizador da RI. 2,6 Já face a forças de rotação externa (RE), o LCMp e o LCMs são os estabilizadores principais em todo o arco, e LOP contribui em extensão. 2,4,6,9 O SM, ao promover a RI da tíbia e ao tensionar estruturas do CPM com a flexão do joelho, torna-se num estabilizador dinâmico face a forças de RE e de translação anterior da tíbia.…”
Section: Introductionunclassified